Optimalisasi Pelayanan Perizinan dengan Sistem Online Single Submission (OSS) dalam Mempercepat Pembangunan di Kota Bima - Nurlaila Nurlaila; Nurhasanah Nurhasanah; Zuriatin Zuriatin (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
This study aims to evaluate the effectiveness of the Online Single Submission (OSS) system in enhancing licensing services and accelerating development in Bima City. Employing a qualitative descriptive approach, the research collected data through interviews, observations, and documentation, analyzing the implementation of OSS at the Investment and Integrated One-Stop Service Office (DPMPTSP). The results indicate that the implementation of OSS has improved the speed, accuracy, transparency, and accessibility of licensing services. The licensing process, which previously took a long time, can now be completed within a maximum of one week. Digital socialization and real-time tracking features have also improved public understanding and reduced misuse of authority. However, the effectiveness of OSS is still hindered by several challenges, such as limited staff, inadequate budget, technical disruptions, and digital divides. Technical issues like system and network disruptions, along with resistance to change, further obstruct the process. To address these challenges, improvements in technology infrastructure, competency training, and increased transparency are required. Overall, although OSS has had a positive impact, further efforts are needed to overcome existing challenges to ensure the system's optimization in supporting the acceleration of development in Bima City.